Impact of post-harvest treatment on shelf-life and quality of mango (Mangifera indica) cv. Langra (Current Horticulture, 2024)
The experiment was conducted on six thousand fruits of mango (Mangifera indica L.) cv. Langra at Fruit Research Station Kuthulia, Rewa, Madhya Pradesh, during 2012 to find out the effect of post-harvest treatment on their shelf-life and quality. The treatments comprised MH- (1000 ppm), GA3 (250 ppm), hot water (50 + °C), potassium permanganate, silver nitrate (1%), wax emulsion coating (6%), neem oil, perforated polythene and the control. The data were recorded on two parameters, viz. physical and chemical at an interval of 4 days for a total period of 12 days during storage. The maximum stone weight (12.68 g) was observed in hot water (50 + °C), while minimum stone weight (11.89 g) was noted in perforated polythene (11.89%). The pulp thickness was maximum due to potassium permagnate (1.43 cm). The maximum TSS was showed by potassium permanganate (19.51°Brix). While minimum TSS (17.58°Brix) was noted in the control. The maximum shelf-life at room temperature was recorded in potassium permanganate (13.87 days), while minimum shelf-life was at room temperature in the control. The maximum acidity was found in potassium permanganate (0.44%), while minimum acidity(0.35%) was recorded with hot water (50 + 2°C).
Keywords: Shelf-life; Potassium permanganate; Silver nitrate; Pulp; Perforated polythene